PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI ALFAMART (STUDI KASUS PADA KONSUMEN ALFAMART DI PERUMNAS MANDALA MEDAN) - GLORIA J.M SIANIPAR (LP2MTBM MAKARIOZ, 2019)
This study aims to determine the effect of price and service quality on customer satisfaction at Alfamart Perumnas Mandala Medan. The variables used are (1) price, (2) service quality and (3) customer satisfaction. The sampling method used in this study uses accidental sampling. The population in this study were all consumers who shop at Alfamart Housing Mandala Medan while the sample in this study were 100 respondents. The approach and analytical technique used in this study are multiple regression analysis, partial test and simultaneous testing using the SPSS software for Windows version 20. Based on the results of the study, the regression equation is obtained as follows: Y = 2, 063 + 0.110 X1 + 0.240 X2. The value of α is 2.063, meaning that all independent variables namely price and service quality have a positive influence on the dependent variable, namely customer satisfaction. From the calculation results of the t (partial) price test (X1) has a positive and significant effect on customer satisfaction, this is indicated by the results of the calculation of the value of tcount = 2.308> t table = 1.660 with a significant of 0.001, <0.05. Service quality variable (X2) has a positive and significant effect on customer satisfaction, this is indicated by the results of the calculation of the value of t count = 4.017> t table = 1,660 with a significant value of 0,000, <0.05. Simultaneously, the price variable (X1) and service quality (X2) have a positive and significant influence on customer satisfaction. This is shown from the results of the calculation of Fcount = 24, 987> Ftable = 3.09 with a significance value of 0,000 <of 0.05. From the results of determination (R2) obtained the value of R2 = 42.1% variable customer satisfaction (Y) is influenced by price and service quality, while the remaining 57.9% is influenced by other independent variables not examined in this study.